Clinico-epidemiological study of childhood stroke in Children Welfare Teaching Hospital/Baghdad - Hammoodi, Husham Z.; Hammoodi, Lamyaa A.; Al-Mahdawi, Akram M. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: The annual incidence of stroke in children after the newborn period is approximately 2.3 per 100000. Half are ischemic, and half are non-traumaticintracerebral and subarchnoidal hemorrhages.Objectives: To study the etiologic factors, clinical presentation andoutcome of stroke among children admitted to children welfare teaching hospital/Baghdad.Patient and methods: A prospective study was carried out in Children Welfare Teaching Hospital;Children age ranged between 1 month -13 years and was admitted to pediatric neurology ward between 1st of November 2013 and 1st of November 2014. After carful clinical history, physical and neurological examinations, the diagnosis of brain stroke was confirmed in all patients by computerized tomography (CT) and/or magnetic resonance imaging (MRI). Patients included in this study were those diagnosed as having ischemic stroke, hemorrhagic stroke.Results: The total number of cases were 61, 36 were male (59%). The age at onset ranged from 1-156 months. Ischemic stroke constituted 39 patients (63.9%). The most common etiologic factors for the ischemic stroke were protein C deficiency (9, 23.1%). The most common etiologic factor for hemorrhage was bleeding disorders in about 50% of patients. The most common presenting features were hemiplegia, seizure, alteration of consciousness; Cranial nerves palsy is mostly present in the ischemic stroke (14,35.9%) and only in one patient (4.5%) of hemorrhagic stroke.Conclusions: Ischemic stroke is more common than hemorrhagic stroke in pediatric age group. The significant risk factors for ischemic stroke are protein C deficiency, Congenital heart disease(CHD) and positive family history, while vitamin K deficiency, prolong Partial thromboplastin time (PTT) and trauma are significant for hemorrhagic stroke. The most common clinical features of both types of stroke are hemiparesis, siezure and alteration of consciousness.